2020
DOI: 10.1101/2020.09.15.298844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing of Batch Chlamydomonas Cultures Reveals Heterogeneity in their Diurnal Cycle Phase

Abstract: The photosynthetic unicellular alga Chlamydomonas (Chlamydomonas reinhardtii) is a versatile reference for algal biology because of the facility with which it can be cultured in the laboratory. Genomic and systems biology approaches have previously been used to describe how the transcriptome responds to environmental changes, but this analysis has been limited to bulk data, representing the average behavior from pools of cells. Here, we apply single-cell RNA sequencing (scRNA-seq) to probe the heterogeneity of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Hopefully, future studies will reveal which cell-specific clocks are sensing and gating these environmental cues, and how they are transmitted across tissues. At least in the case of Chlamydomonas, single-cell sequencing uncovered a later diurnal phase in irondeficient cells (Ma et al, 2021) that is consistent with the long period observed in Arabidopsis plants under ironlimiting conditions (Chen et al, 2013;Hong et al, 2013;Salom e et al, 2013). This certainly argues for considering individual cell phase when determining the cell state, especially in multicellular organisms where phase response is likely dependent on cell identity.…”
Section: Environmental Signaling Happens In the Context Of Developmen...supporting
confidence: 64%
See 1 more Smart Citation
“…Hopefully, future studies will reveal which cell-specific clocks are sensing and gating these environmental cues, and how they are transmitted across tissues. At least in the case of Chlamydomonas, single-cell sequencing uncovered a later diurnal phase in irondeficient cells (Ma et al, 2021) that is consistent with the long period observed in Arabidopsis plants under ironlimiting conditions (Chen et al, 2013;Hong et al, 2013;Salom e et al, 2013). This certainly argues for considering individual cell phase when determining the cell state, especially in multicellular organisms where phase response is likely dependent on cell identity.…”
Section: Environmental Signaling Happens In the Context Of Developmen...supporting
confidence: 64%
“…In systems with just one cell‐type identity, changes in cell state can be clearly detected. For example, through single‐cell sequencing of Chlamydomonas cell culture over time, the transcriptional changes driven by iron limitation and the circadian clock could be easily discerned (Ma et al., 2021). However, in multicellular systems, where many different cell identities exist, it is more difficult to dissociate cell identity from cell state.…”
Section: Developmental Pseudotime: Predicting the Past From Plant Cel...mentioning
confidence: 99%
“…scPrisma detects and filters the diurnal cycle in Chlamydomonas. (A) PCA representation of cells in spectrally enhanced cyclic signal of the iron replete (Fe+) experiment [27]. Each plot represents 1/6 of the 24 hours cycle.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the use of scPrisma for more complex systems with diverse prior knowledge, we next turn our attention to scRNA-seq data collected for Chlamydomonas (green algae), grown under two contrasting conditions, iron replete (Fe+) and iron deficient (Fe-) [27]. In both conditions, a signal in the gene expression of the Chlamydomonas that reflects the 24 hours diurnal cycle was previously detected [27]. To evaluate progression of cells along the diurnal cycle, we used marker genes corresponding to different cycle phases obtained from bulk RNA-sequencing [44] (Supplementary A.5).…”
Section: Scprisma Detects and Filters The Diurnal Cycle In Chlamydomonasmentioning
confidence: 99%
“…The dataset was filtered for genes that met minimum read count cutoffs of at least 10 mapped reads in at least 10% of the samples, resulting in 15,541 genes for downstream analyses. Two-dimensional Uniform Manifold Approximation and Projection (UMAP) was used to reveal clusters of RNA-seq data (Ma et al, 2021).…”
Section: Transcriptomicsmentioning
confidence: 99%